NMDA receptor antagonists ketamine and Ro25-6981 inhibit evoked release of glutamate in vivo in the subiculum - Stan, T L (Nature Publishing Group, 2014)
Preclinical and clinical data have identified ketamine, a non-selective NMDAR (N-methyl-D-aspartate receptor) antagonist, as a promising medication for patients who do not respond to treatment with monoamine-based antidepressants. Moreover, unlike the current monoamine-based antidepressants, ketamine has a long-lasting effect already after a single dose. The mechanisms of ketamine action remain to be fully understood. Using a recently developed microelectrode array (MEA), which allows sub-second measurements of fluctuating glutamate concentrations, we studied here the effects of in vivo local application of the ketamine and of the N2B subunit-specific antagonist Ro25-6981 upon evoked glutamate release. Both ligands inhibit glutamate release in subregions of the hippocampus and prefrontal cortex. Likewise, acute systemic ketamine treatment, at an antidepressant dose, caused a reduction in evoked glutamate release in the subiculum. We suggest that the effects of ketamine and Ro25-6981 in the subiculum could involve blockade of presynaptic NMDA receptors containing N2B subunits.